2011
DOI: 10.15193/zntj/2011/76/143-152
|View full text |Cite
|
Sign up to set email alerts
|

SENSORY & MICROBIOLOGICAL ASSESSMENT OF TURKEY HENS BREAST MUSCLES DEPENDING ON METHOD AND TIME OF COLD STORAGE

Abstract: S t r e s z c z e n i eNowoczesną metodą przedłużania trwałości mięsa jest chłodnicze przechowywanie w kontrolowanej atmosferze. Celem pracy było określenie wpływu dwóch metod przechowywania mięśni piersiowych indyczek: w atmosferze gazów kontrolowanych o składzie 95 % azotu i 5 % tlenu oraz w powietrzu atmosferycznym o temp. 2 ºC, w ciągu od 5 do 25 dób, na ich właściwości sensoryczne oraz ogólną liczbę drobnoustrojów. W wyniku przeprowadzonych badań stwierdzono, że stopień zanieczyszczenia mikrobiologicznego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…Poultry meat with a low pH has been associated with low water holding capacity (WHC), which results in increased cook loss, drip loss, and shelf life, and decreased tenderness. Similar results were noted in the research of Ruíz-Cruz et al [62], and Chmiel and Słowi ński [6], as well as Kondratowicz et al [30].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Poultry meat with a low pH has been associated with low water holding capacity (WHC), which results in increased cook loss, drip loss, and shelf life, and decreased tenderness. Similar results were noted in the research of Ruíz-Cruz et al [62], and Chmiel and Słowi ński [6], as well as Kondratowicz et al [30].…”
Section: Resultssupporting
confidence: 89%
“…The effects of cool storage conditions on the sensory conditions of poultry meat were presented in the research of Chmiel and Słowi ński [6], Ruíz-Cruz et al [62], Yimenu et al [36], Sujiwo et al [7], and Kondratowicz et al [30], as well as Garavito et al [16]. In the study we conducted, over the storage time, all of the tested sensory characteristics of meat deteriorated, i.e., the intensity and desirability of odour, colour, texture, and general appearance (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a study by Kondratowicz et al (2011), chilled muscles received higher scores in a sensory evaluation. Mikulski et al (2012) reported a higher shear force value (19.10 N) in the breast muscles of control group turkeys.…”
Section: The Effect Of Lycopene Addition On the Chemical Compositionmentioning
confidence: 82%